PENYULUHAN PEMBERIAN BABY MASSAGE DALAM MENINGKATKAN KUALITAS TIDUR BAYI USIA 11 - 25 BULAN DI POSYANDU HARAPAN BUNDA - Eka Widya Ningrum; Arif Pristianto (LPPM Universitas Abdurrab, 2021)
Sleep is one of the very important needs for babies, because good sleep quality helps the optimal growth and development process. One of the ways used to improve the quality of baby sleep by giving baby massage. Baby massage technique is to give a soft touch to the baby's skin in order to stimulate blood circulation and increase the energy of more oxygen waves to the brain so as to spur better circulation and respiration system. Relaxing and comfortable feeling due to massage touch is able to improve the quality of baby's sleep, increase immunity or immunity and increase the baby's weight. The purpose of this activity is to find out the benefits of baby massage in improving the quality of sleep of infants aged 11 - 25 months. Method of counseling activities by providing education in posyandu hope mother and make a visit to the mother's house for the giving of baby massage and share questionnaire. The results of this counseling activity obtained the level of knowledge of mothers about the role of physiotherapy and the benefits of baby massage in the category of less with a percentage of 59% and the quality of sleep in toddlers averaged in the good category with a percentage of 73%. Conclusion of this counseling activity that the administration of baby massage is able to improve the quality of sleep of infants aged 11 - 25 months.